Technical Evolution of Medical Endoscopy - S. Gross (Acta Polytechnica, 2009)
This paper gives a summary of the technical evolution of medical endoscopy. The first documented redirection of sunlight into the human body dates back to the 16th century. Rigid tubes with candle light were given a trial later on. Low light intensity forced the development of alternative light sources. Some of these experiments included burning chemical components. Electric lighting finally solved the problems of heat production and smoke. Flexible endoscopy increased the range of medical examinations as it allowed access to tight and angular body cavities. The first cameras for endoscopic applications made taking photos from inside the human body possible. Later on, digital video endoscopy made endoscopes easier to use and allowed multiple spectators to observe the endoscopic intervention. Swallowable capsules called pill-cams made endoscopic examinations of the small intestine possible. Modern technologies like narrow band imaging and fluorescence endoscopy increased the diagnostic significance of endoscopic images. Today, image processing is applied to decrease noise and enhance image quality. These enhancements have made medical endoscopy an invaluable tool in many diagnostic processes. In closing, an example is given of an interdisciplinary examination, which is taken from the archaeological field.